The Effect of Leadership, Work Discipline and Motivation on Employee Performance (Study at PT. Kukar Sejahtera Dambaan Etam (Perseroda) Kutai Kertanegara Regency, East Kalimantan) - Ariffudin Ariffudin; Sulastini Sulastini; Maskur Maskur (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Focus on three issues, namely (1) Whether there is a partial influence of leadership on employee performance at the PT. Kukar Sejahtera Dambaan Etam (Perseroda) Kutai Kertanegara Regency, (2) Is there a partial influence of motivation on employee performance at PT. Kukar Sejahtera Dambaan Etam (Perseroda), (3) Is there a partial influence of work discipline on employee performance at PT. Kukar Sejahtera Dambaan Etam (Perseroda) Kutai Kertanegara Regency and (3) Whether there is an influence of leadership, motivation and discipline together on employee performance at PT. Kukar Sejahtera Dambaan Etam (Perseroda). Method: This study uses a quantitative approach. The number of samples taken was 48 respondents with a saturated sampling technique. Data collection techniques use questionnaires (questionnaires), while data analysis uses multiple linear regression. The results showed that there was a significant partial influence of leadership on employee performance at PT. Kukar Sejahtera Dambaan Etam (Perseroda), there is a significant partial influence of motivation on employee performance at PT. Kukar Sejahtera Dambaan Etam (Perseroda), there is a significant partial influence of work discipline on employee performance at PT. Kukar Sejahtera Dambaan Etam (Perseroda) Kutai Kertanegara Regency, and there is a significant influence simultaneously on leadership, motivation and work discipline on employee performance at PT. Kukar Sejahtera Dambaan Etam (Perseroda) Kutai Kertanegara Regency Keywords: Leadership, Motivation, Work Discipline, Employee Performance